Preparation method of UIO-66-NH2 modified polyphenylene sulfide needled felt and PM2.5 filtration of UIO-66-NH2 modified polyphenylene sulfide needled felt
The UIO-66-NH2 nanocrystals were attached to the PPS needle felt through electrospraying technology, which solved the problems of low efficiency and poor temperature resistance of traditional filter materials, and achieved efficient and stable PM2.5 filtration and simple preparation process , suitable for industrial applications.
Patent Information
- Application Number
- CN202411386978.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-03
AI Technical Summary
Traditional filter materials have low efficiency, short service life and poor temperature resistance in removing PM2.5. MOF modified activated carbon has problems such as unsolid bonding and poor dispersion, and the in-situ growth method is complex and difficult to produce on a large scale.
The UIO-66-NH2 nanocrystals are uniformly attached to the surface of PPS needle felt by electrospraying technology to form a stable and efficient composite PPS fiber material. The sandwich structure is formed by pre-needle puncture, and combined with sol spraying growth method and heat treatment, the MOFs and The bonding of substrates.
It improves filtration efficiency and chemical and thermal stability of the material, simplifies the preparation process, reduces costs, is suitable for large-scale production, and maintains high-efficiency filtration performance under high-temperature environments.
Smart Images

Figure CN119243476A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of air filter materials, and particularly relates to a method of using UIO-66-NH 2 Preparation technology of metal organic framework material modified polyphenylene sulfide needle felt, and the use of this material in high-efficiency PM2.5 filtration applications. Background Art
[0002] Traditional filter materials have problems such as low efficiency, short service life and poor temperature resistance in removing PM2.5. In order to meet these challenges, researchers have been exploring new filter materials to improve filtration efficiency, extend service life and enhance high temperature resistance.
[0003] MOFs materials have wide application potential in gas separation and adsorption due to their porosity, high specific surface area and adjustable pore size. Therefore, Chinese patent 202011255092.X proposes a method for preparing MOF-modified activated carbon bricks, which prepares air filter materials with high adsorption performance by dispersing MOF raw materials and impregnating activated carbon bricks, thus solving the problem of large wind resistance of activated carbon.
[0004] Chinese patent 202010503971.3 discloses a repeatedly washable composite air filter material. This technology utilizes polypropylene / polycarbonate mixed masterbatch, grows ZIF-8 on the filter material through melt-blowing technology and in-situ growth method, and finally composites it into PPC / PVDF / ZIF-8 filter material, which can maintain stable PM2.5 filtration performance even when exposed to water.
[0005] However, MOF-modified activated carbon has some defects in industrial gas filtration, such as the combination of MOF and activated carbon may not be strong enough, poor dispersion, and stability in extreme environments needs to be improved. In addition, the in-situ growth method of MOF may require special equipment such as autoclaves, and the preparation process is complicated and difficult to scale up.
[0006] In order to solve the above challenges, the present invention adopts electrospraying technology, selects high-performance PPS needle felt as the substrate, and introduces UIO-66-NH 2 MOFs materials. Summary of the invention
[0007] In view of the shortcomings of the prior art, the present invention proposes an innovative UIO-66-NH 2 Preparation method of modified PPS needle felt. Compared with the preparation of traditional industrial gas filter materials, this method has the advantages of simple operation, high preparation efficiency and wide applicability. 2The nanocrystals are evenly and firmly attached to the surface of the PPS needle-punched felt, forming a composite PPS fiber material with stable structure, high temperature resistance and high efficiency filtering performance.
[0008] To achieve the above object, the present invention is implemented through the following technical solutions:
[0009] A UIO-66-NH 2 The preparation method of modified polyphenylene sulfide needle felt and its application in PM2.5 filtration are characterized in that the method comprises the following steps:
[0010] Step 1: Mix 0.8dtex×38mm polyphenylene sulfide microfibers, open and comb them to form a uniform fiber web and glass fiber base cloth, and feed them into the needle punching machine for pre-needling and one needling, so that the fibers are interlaced and form a felt-like structure. The multiple needles in the needle punching equipment will pass through the fiber layer, so that the fibers are connected longitudinally and transversely, and form a three-layer sandwich structure;
[0011] Step 2, dissolving the organic amino ligand and zirconium chloride in N,N-dimethylformamide respectively, mixing the two solutions, adding a regulator and performing ultrasonication;
[0012] Step 3: The prepared sandwich structure polyphenylene sulfide needle felt is thoroughly pre-treated and cleaned to remove surface impurities, and then laid flat after drying. The sprayed needle felt is placed in a hot air drying oven for heat treatment for 1-2 hours using the sol-gel spray growth method on the dust-facing side, and UIO-66-NH is loaded on the surface of the polyphenylene sulfide needle felt. 2 ;
[0013] Step 4: Then load the above surface with UIO-66-NH 2 The polyphenylene sulfide needled felt was washed with N,N-dimethylformamide, anhydrous ethanol and deionized water in sequence, and then dried in an electric blast drying oven at 40-60°C.
[0014] Preferably, the frequency of pre-acupuncture in step 1 is 80 punctures / min; the frequency of main acupuncture is 120 punctures / min, the number of acupuncture paths is 2, and the acupuncture depth is 5 mm.
[0015] Preferably, the base fabric layer in step 1 is a glass fiber mesh cloth having a thickness of 1-1.5 mm, formed by opening and combing glass fibers with a thickness of 1.2 dtex and a length of 51 mm to form a uniform fiber web.
[0016] Preferably, in step 2, zirconium chloride and the organic amino ligand are dissolved in N,N-dimethylformamide at a molar ratio of 1:1-3, and a certain amount of a regulator is added to prepare a reactant solution.
[0017] Preferably, the organic amino ligand in step 2 comprises 2-aminoterephthalic acid or 2,5-diaminoterephthalic acid.
[0018] Preferably, the regulator in step 2 includes one or more of formic acid, glacial acetic acid and hydrochloric acid.
[0019] Preferably, in step 2, the volume ratio of the regulator to the mixed solution of the organic amino ligand solution and the zirconium chloride salt solution is 1:10-40.
[0020] Preferably, in step 2, the ultrasonic temperature of the mixed solvent is 20-60° C. and the ultrasonic frequency is 70-90%.
[0021] Preferably, in step 3, the inner diameter of the nozzle is less than or equal to 6 mm, the spraying voltage is controlled at 1 kV-30 kV, and the spraying distance is maintained at 10-15 cm. In order to spray evenly, the spray gun moves slowly back and forth from left to right.
[0022] Compared with the prior art, the present invention has the following beneficial technical effects:
[0023] Enhanced filtration efficiency: Electrospraying technology ensures that UIO-66-NH 2 The uniform distribution of crystals on the substrate surface improves the loading efficiency of MOFs and the overall performance of the filtration material.
[0024] Improved chemical stability: Through electrospraying technology, the bond between MOFs and PPS needle felt is more firmly established under the action of electrostatics, which enhances the chemical and thermal stability of the material during long-term use and makes it suitable for extreme environmental conditions.
[0025] Ease of operation: The preparation process adopted by the present invention is concise and easy to implement, which effectively reduces the manufacturing cost and improves the production efficiency. It is suitable for large-scale production and helps to meet the large demand for high-performance filter materials in industrial applications.
[0026] The invention provides a wide range of application potential and flexibility by integrating electrostatic spraying technology with MOFs materials, and is applicable to a variety of substrates and MOFs types. At the same time, the technology usually uses less solvent, which helps reduce environmental pollution during the production process. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Schematic diagram of the structure of the electrospraying device.
[0028] Figure 2 UIO-66-NH 2 Filtration efficiency of modified polyphenylene sulfide needle felt for PM2.5. DETAILED DESCRIPTION
[0029] The present invention is described in detail below in conjunction with the accompanying drawings, but it should be noted that the implementation of the present invention is not limited to the following embodiments.
[0030] Example 1
[0031] A UIO-66-NH 2 The preparation method of modified polyphenylene sulfide needled felt and its PM2.5 filtration are characterized by comprising the following steps:
[0032] Step 1: Mix 0.8dtex×38mm polyphenylene sulfide microfibers, open and comb them to form a uniform fiber web and glass fiber base cloth, and feed them into the needle punching machine for pre-needling and one needling, so that the fibers are interlaced and form a felt-like structure. The multiple needles in the needle punching equipment will pass through the fiber layer, so that the fibers are connected longitudinally and transversely, and form a three-layer sandwich structure;
[0033] Step 2, dissolving the organic amino ligand and zirconium chloride in N,N-dimethylformamide respectively, mixing the two solutions, adding a regulator and performing ultrasonication;
[0034] Step 3: The prepared sandwich structure polyphenylene sulfide needle felt is thoroughly pre-treated and cleaned to remove surface impurities, and then laid flat after drying. The sprayed needle felt is placed in a hot air drying oven for heat treatment for 1 hour using the sol-gel spray growth method on the dust-facing side, and UIO-66-NH 2 ;
[0035] Step 4: Then load the above surface with UIO-66-NH 2 The polyphenylene sulfide needled felt was washed with N,N-dimethylformamide, anhydrous ethanol and deionized water in sequence, and then dried in an electric blast drying oven at 40°C.
[0036] Preferably, the frequency of pre-acupuncture in step 1 is 80 punctures / min; the frequency of main acupuncture is 120 punctures / min, the number of acupuncture paths is 2, and the acupuncture depth is 5 mm.
[0037] Preferably, the base fabric layer in step 1 is a glass fiber mesh cloth with a thickness of 1.2 mm, which is formed by opening and combing glass fibers with a thickness of 1.2 dtex and a length of 51 mm to form a uniform fiber web.
[0038] Preferably, in step 2, zirconium chloride and the organic amino ligand are dissolved in N,N-dimethylformamide in a molar ratio of 1:1, and a certain amount of a regulator is added to prepare a reactant solution.
[0039] Preferably, the organic amino ligand in step 2 is 2-aminoterephthalic acid.
[0040] Preferably, the regulator in step 2 comprises formic acid.
[0041] Preferably, in step 2, the volume ratio of the regulator to the mixed solution of the organic amino ligand solution and the zirconium chloride salt solution is 1:20.
[0042] Preferably, in step 2, the ultrasonic temperature of the mixed solvent is 20° C. and the ultrasonic frequency is 70%.
[0043] Preferably, in step 3, the heat temperature of the hot air drying oven is 120°C.
[0044] Preferably, in step 3, the inner diameter of the nozzle is 4 mm, the spraying voltage is controlled at 10 kV, and the spraying distance is maintained at 10 cm. In order to spray evenly, the spray gun moves slowly back and forth from left to right so that UIO-66-NH 2 .
[0045] UIO-66-NH prepared by the present invention 2 Modified polyphenylene sulfide needle felt significantly increases the effective filtration area of the filter material, thereby improving the filtration accuracy while maintaining low filtration resistance. The filter material can work stably in a high temperature environment of over 260°C, achieving a filtration efficiency of up to 90.6%, and the resistance pressure drop is optimized to only 65.5Pa, demonstrating its excellent performance in the field of high-efficiency air filtration.
[0046] Example 2
[0047] A UIO-66-NH 2 The preparation method of modified polyphenylene sulfide needled felt and its PM2.5 filtration are characterized by comprising the following steps:
[0048] Step 1: Mix 0.8dtex×38mm polyphenylene sulfide microfibers, open and comb them to form a uniform fiber web and glass fiber base cloth, and feed them into the needle punching machine for pre-needling and one needling, so that the fibers are interlaced and form a felt-like structure. The multiple needles in the needle punching equipment will pass through the fiber layer, so that the fibers are connected longitudinally and transversely, and form a three-layer sandwich structure;
[0049] Step 2, dissolving the organic amino ligand and zirconium chloride in N,N-dimethylformamide respectively, mixing the two solutions, adding a regulator and performing ultrasonication;
[0050] Step 3: The prepared sandwich structure polyphenylene sulfide needle felt is thoroughly pre-treated and cleaned to remove surface impurities, and then laid flat after drying. The sprayed needle felt is placed in a hot air drying oven for heat treatment for 1.5 hours using the sol spray growth method on the dust-facing side, and UIO-66-NH 2 ;
[0051] Step 4: Then load the above surface with UIO-66-NH 2 The polyphenylene sulfide needled felt was washed with N,N-dimethylformamide, anhydrous ethanol and deionized water in sequence, and then dried in an electric blast drying oven at 50°C.
[0052] Preferably, the frequency of pre-acupuncture in step 1 is 80 punctures / min; the frequency of main acupuncture is 120 punctures / min, the number of acupuncture paths is 2, and the acupuncture depth is 5 mm.
[0053] Preferably, the base fabric layer in step 1 is a glass fiber mesh cloth with a thickness of 1.2 mm, which is formed by opening and combing glass fibers with a thickness of 1.2 dtex and a length of 51 mm to form a uniform fiber web.
[0054] Preferably, in step 2, zirconium chloride and the organic amino ligand are dissolved in N,N-dimethylformamide at a molar ratio of 1:2, and a certain amount of a regulator is added to prepare a reactant solution.
[0055] Preferably, the organic amino ligand in step 2 is 2,5-diaminoterephthalic acid.
[0056] Preferably, the regulator in step 2 comprises glacial acetic acid.
[0057] Preferably, in step 2, the volume ratio of the regulator to the mixed solution of the organic amino ligand solution and the zirconium chloride salt solution is 1:30.
[0058] Preferably, in step 2, the ultrasonic temperature of the mixed solvent is 25° C. and the ultrasonic frequency is 80%.
[0059] Preferably, in step 3, the heat temperature of the hot air drying oven is 150°C.
[0060] Preferably, in step 3, the inner diameter of the nozzle is 4 mm, the spraying voltage is controlled at 15 kV, and the spraying distance is maintained at 12 cm. In order to spray evenly, the spray gun moves slowly back and forth from left to right so that UIO-66-NH 2 .
[0061] UIO-66-NH prepared by the present invention 2 Modified polyphenylene sulfide needled felt significantly increases the effective filtration area of the filter material, thereby improving the filtration accuracy while maintaining low filtration resistance. The filter material can work stably in a high temperature environment of over 260°C, achieving a filtration efficiency of up to 93.4%, and the resistance pressure drop is optimized to only 67.2Pa, demonstrating its excellent performance in the field of high-efficiency air filtration.
[0062] Example 3
[0063] A UIO-66-NH 2 The preparation method of modified polyphenylene sulfide needled felt and its PM2.5 filtration are characterized by comprising the following steps:
[0064] Step 1: Mix 0.8dtex×38mm polyphenylene sulfide microfibers, open and comb them to form a uniform fiber web and glass fiber base cloth, and feed them into the needle punching machine for pre-needling and one needling, so that the fibers are interlaced and form a felt-like structure. The multiple needles in the needle punching equipment will pass through the fiber layer, so that the fibers are connected longitudinally and transversely, and form a three-layer sandwich structure;
[0065] Step 2, dissolving the organic amino ligand and zirconium chloride in N,N-dimethylformamide respectively, mixing the two solutions, adding a regulator and performing ultrasonication;
[0066] Step 3: The prepared sandwich structure polyphenylene sulfide needle felt is thoroughly pre-treated and cleaned to remove surface impurities, and then laid flat after drying. The sprayed needle felt is placed in a hot air drying oven for heat treatment for 2 hours using the sol-gel spray growth method on the dust-facing side, and UIO-66-NH 2 ;
[0067] Step 4: Then load the above surface with UIO-66-NH 2 The polyphenylene sulfide needled felt was washed with N,N-dimethylformamide, anhydrous ethanol and deionized water in sequence, and then dried in an electric blast drying oven at 60°C.
[0068] Preferably, the frequency of pre-acupuncture in step 1 is 80 punctures / min; the frequency of main acupuncture is 120 punctures / min, the number of acupuncture paths is 2, and the acupuncture depth is 5 mm.
[0069] Preferably, the base fabric layer in step 1 is a glass fiber mesh cloth with a thickness of 1.2 mm, which is formed by opening and combing glass fibers with a thickness of 1.2 dtex and a length of 51 mm to form a uniform fiber web.
[0070] Preferably, in step 2, zirconium chloride and the organic amino ligand are dissolved in N,N-dimethylformamide at a molar ratio of 1:3, and a certain amount of a regulator is added to prepare a reactant solution.
[0071] Preferably, the organic amino ligand in step 2 is 2,5-diaminoterephthalic acid.
[0072] Preferably, the regulator in step 2 comprises concentrated hydrochloric acid.
[0073] Preferably, in step 2, the volume ratio of the regulator to the mixed solution of the organic amino ligand solution and the zirconium chloride salt solution is 1:40.
[0074] Preferably, in step 2, the ultrasonic temperature of the mixed solvent is 30° C. and the ultrasonic frequency is 90%.
[0075] Preferably, the heat temperature of the hot air drying oven in step 3 is 180°C.
[0076] Preferably, in step 3, the inner diameter of the nozzle is 4 mm, the spraying voltage is controlled at 20 kV, and the spraying distance is maintained at 15 cm. In order to spray evenly, the spray gun moves slowly back and forth from left to right so that UIO-66-NH 2 .
[0077] UIO-66-NH prepared by the present invention 2 Modified polyphenylene sulfide needled felt significantly increases the effective filtration area of the filter material, thereby improving the filtration accuracy while maintaining low filtration resistance. The filter material can work stably in a high temperature environment of over 260°C, achieving a filtration efficiency of up to 93%, and the resistance pressure drop is optimized to only 68Pa, demonstrating its excellent performance in the field of high-efficiency air filtration.
[0078] As described above, these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. Any simple modification, change and equivalent structural change made to the above embodiments according to the technical essence of the invention still fall within the protection scope of the technical solution of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing UIO-66-NH2 modified polyphenylene sulfide needled felt and its application in PM2.5 filtration, characterized in that: The following steps are involved: (1) Mix 0.8dtex×38mm polyphenylene sulfide microfibers and open and comb them to form a uniform fiber web and glass fiber base cloth, then feed them into a needle loom for pre-needling and one needling, so that the fibers are intertwined and form a felt-like structure. The multiple needles in the needling device penetrate the fiber layers, connecting the fibers longitudinally and transversely and forming a three-layer sandwich structure; (2) Dissolve the organic amino ligand and zirconium chloride in N,N-dimethylformamide respectively, mix the two solutions, add the regulator and perform ultrasonication; (3) The prepared sandwich structure polyphenylene sulfide needle felt is thoroughly pre-treated and cleaned to remove surface impurities, and then laid flat after drying. The sprayed needle felt is placed in a hot air drying oven for heat treatment for 1-2 hours using the sol-gel spray growth method on the dust-facing side, and UIO-66-NH2 is loaded on the surface of the polyphenylene sulfide needle felt; (4) Then the polyphenylene sulfide needle-punched felt with UIO-66-NH2 loaded on the surface was washed with N,N-dimethylformamide, anhydrous ethanol and deionized water in sequence, and then dried in an electric blast drying oven at 40-60°C.
2. The preparation method of a UIO-66-NH2 modified polyphenylene sulfide needled felt according to claim 1 and its application in PM2.5 filtration, characterized in that: The acupuncture frequency of the pre-acupuncture in step (1) is 80 punctures / min; the acupuncture frequency of the main acupuncture is 120 punctures / min, the number of acupuncture paths is 2, and the acupuncture depth is 5 mm.
3. The preparation method of a UIO-66-NH2 modified polyphenylene sulfide needled felt according to claim 1 and its application in PM2.5 filtration, characterized in that: In the step (2), zirconium chloride and the organic amino ligand are dissolved in N,N-dimethylformamide in a molar ratio of 1:1-3, and a certain amount of a regulator is added to prepare a reactant solution.
4. The preparation method of a UIO-66-NH2 modified polyphenylene sulfide needled felt according to claim 1 and its application in PM2.5 filtration, characterized in that: In the step (2), the ultrasonic temperature is 20-60° C. and the ultrasonic frequency is 70-90%.
5. The preparation method of a UIO-66-NH2 modified polyphenylene sulfide needled felt and its application in PM2.5 filtration according to claim 1, characterized in that: In the step (2), the volume ratio of the regulator to the mixed solution of the organic amino ligand solution and the zirconium chloride salt solution is 1:10-40.
6. The preparation method of a UIO-66-NH2 modified polyphenylene sulfide needled felt and its application in PM2.5 filtration according to claim 2, characterized in that: The uniformly mixed solution in step (3) is poured into a spray bottle, and the spray gun is aimed at the horizontally placed needle felt for one-step spraying. The inner diameter of the nozzle is less than or equal to 6 mm, the spraying voltage is controlled at 1 kV-30 kV, and the spraying distance is maintained at 10-15 cm. In order to spray uniformly, the spray gun is slowly moved back and forth from left to right.
Citation Information
Patent Citations
High-temperature-resistant superfine composite fiber air purification textile and preparation method thereof
CN110552114A
UIO-66-X-loaded glass fiber compound as well as preparation method and application thereof
CN113769714A
Preparation method of ZIF-8 / PTFE composite filter membrane
CN118649562A
Preparation method of ZIF-8 modified high-temperature-resistant composite nanofiber membrane
CN118650945A
